2017
DOI: 10.1515/phys-2017-0125
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and application of coaxial polyvinyl alcohol/chitosan nanofiber membranes

Abstract: It is difficult to fabricate chitosan-wrapped coaxial nanofibers, because highly viscous chitosan solutions might hinder the manufacturing process. To overcome this difficulty, our newly developed method, which included the addition of a small amount of gum arabic, was utilized to prepare much less viscous chitosan solutions. In this way, coaxial polyvinyl alcohol (PVA)/chitosan (as core/shell) nanofiber membranes were fabricated successfully by coaxial electrospinning. The core/shell structures were confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…The negative values of ∆E confirm the partial wetting regime as indicated in [63]. If considering the surface energy of pure water at 25 • C and γ L ≈ 0.72 J/m 2 , the pure gelatin or pure PVA γ S ≈ 0.033-0.29 J/m 2 [64][65][66] and then the interfacial γ SL = (γ S − γ L − ∆E) would be approximately (−0.0259-0.2311 J/m 2 ) and (−0.0146-0.2424 J/m 2 ). The negative values are physically infeasible as the interface between nanofibers and water becomes unstable.…”
supporting
confidence: 69%
“…The negative values of ∆E confirm the partial wetting regime as indicated in [63]. If considering the surface energy of pure water at 25 • C and γ L ≈ 0.72 J/m 2 , the pure gelatin or pure PVA γ S ≈ 0.033-0.29 J/m 2 [64][65][66] and then the interfacial γ SL = (γ S − γ L − ∆E) would be approximately (−0.0259-0.2311 J/m 2 ) and (−0.0146-0.2424 J/m 2 ). The negative values are physically infeasible as the interface between nanofibers and water becomes unstable.…”
supporting
confidence: 69%
“…However, we found that these scaffolds quickly degrade in water-based media, providing only an immediate burst release of drugs. One of the approaches to overcome such challenges is the encapsulation of these gels by a hydrophobic shell polymer using coaxial electrospinning, which can also be used to generate hollow fibers 16,17,38 . A common hydrophobic polymer, polycaprolactone (PCL) is an aliphatic polyester that has been widely investigated for many biomedical applications, including wound healing, owing to its easy processability and biocompatibility 39,40 .…”
mentioning
confidence: 99%
“…and 2910 cm -1 for the stretching vibration of -CH 2 group, 1242, 1088, 1023 and 945 cm -1 (C-O) stretching vibration, respectively [41,48,49]. On the other hand, for the PVA-Gel bers the band appears at 3290 cm -1 for the (-OH) group.…”
Section: Ft-ir Analysismentioning
confidence: 94%